2011
DOI: 10.1371/journal.pone.0027116
|View full text |Cite
|
Sign up to set email alerts
|

Bmi1 Is Expressed in Postnatal Myogenic Satellite Cells, Controls Their Maintenance and Plays an Essential Role in Repeated Muscle Regeneration

Abstract: Satellite cells are the resident stem cell population of the adult mammalian skeletal muscle and they play a crucial role in its homeostasis and in its regenerative capacity after injury. We show here that the Polycomb group (PcG) gene Bmi1 is expressed in both the Pax7 positive (+)/Myf5 negative (−) stem cell population as well as the Pax7+/Myf5+ committed myogenic progenitor population. Depletion of Pax7+/Myf5− satellite cells with reciprocal increase in Pax7+/Myf5+ as well as MyoD positive (+) cells is seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…Since it has previously been demonstrated that Bmi1 is expressed in Pax7-positive satellite cells within muscle (Robson et al, 2011), it is possible that the intramuscular Bmi1 -lineage tumors could arise from this cell population. However, we already discussed that Pax7 CreERT2 ; Rosa26 EA1 do not form tumors, arguing against the possibility that satellite cells provide a potential cell of origin for CCS (Figure S2D and E).…”
Section: Resultsmentioning
confidence: 99%
“…Since it has previously been demonstrated that Bmi1 is expressed in Pax7-positive satellite cells within muscle (Robson et al, 2011), it is possible that the intramuscular Bmi1 -lineage tumors could arise from this cell population. However, we already discussed that Pax7 CreERT2 ; Rosa26 EA1 do not form tumors, arguing against the possibility that satellite cells provide a potential cell of origin for CCS (Figure S2D and E).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the defects of cyclin D3-null satellite cells are similar to those displayed by satellite cells with disrupted function of the Polycomb proteins Ezh2 or Bmi1 51,59. Indeed, Polycomb complexes are known to play a pivotal role in maintaining the self-renewal capability of various adult stem cells by binding directly and repressing the promoter of p16, a specific inhibitor of the activity of cyclin D-dependent kinases 6064.…”
Section: Discussionmentioning
confidence: 96%
“…4B). On the other hand, expression of the muscle stem cell factors Bmi1 (26) and Nestin (27) was decreased when Sfmbt1 was depleted, suggesting a role of Sfmbt1 in the maintenance of the muscle stem cell state. Our findings thus support that Sfmbt1 criti- .…”
Section: Sfmbt1 Represses Transcription Of Muscle Transcription Factomentioning
confidence: 99%